Is There a Role for GPCR Agonist Radiotracers in PET Neuroimaging? - Colom, Matthieu; Vidal, Benjamin; Zimmer, Luc (Frontiers in Molecular Neuroscience, 2019)
Positron emission tomography (PET) is a molecular imaging modality that enables in vivo exploration of metabolic processes and especially the pharmacology of neuroreceptors. G protein-coupled receptors (GPCR) play an important role in numerous pathophysiologic disorders of the central nervous system. Thus, they are targets of choice in PET imaging to bring proof concept of change in density in pathological conditions or in pharmacological challenge. At present, most radiotracers are antagonist ligands. In vitro data suggest that properties differ between GPCR agonists and antagonists: antagonists bind to receptors with a single affinity, whereas agonists are characterized by two different affinities: high affinity for receptors that undergo functional coupling to G-proteins, and low affinity for those that are not coupled. In this context, agonist radiotracers may be useful tools to give functional images of GPCRs in the brain, with high sensitivity to neurotransmitter release. Here we review all existing PET radiotracers and their role for understanding the ligand-receptor paradigm of GPCR in comparison with corresponding antagonist radiotracers.